USER INTERACTION IN CISCO WEBEX APPLICATION BUILDING CUSTOMER ENGAGEMENT BEHAVIOR: CASE STUDY OF STUDENT EXCHANGE PROGRAM INDONESIA-MALAYSIA - Wihartika, Doni; Andria, Fredi; Silviani, Leni (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
The rapid pace of technological advancement is significantly influencing the global digital landscape. The emergence of the COVID-19 pandemic has revolutionized our communication methods, leading to a shift from in-person to online interactions. This transition has necessitated using various platforms such as Cisco Webex, Zoom, and Google Meet for educational and meeting activities. A study was conducted to investigate the subscription behaviour of users towards the Cisco Webex application. Employing an exploratory, descriptive approach and qualitative methods, the research focused on students at the Faculty of Economics and Business at Pakuan University, including Malaysian exchange students. A purposive sample of ten students participated in the study, providing data through interviews. The findings revealed that environmental factors influenced all ten respondents, constituting 100% of the participants.